1980
DOI: 10.1210/endo-107-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine-Induced Changes in Characteristics and Activities of β-Adrenergic Receptors and Adenosine 3′,5′-Monophosphate and Guanosine 3′,5′-Monophosphate Systems in the Heart May Be Related to Reputed Catecholamine Supersensitivity in Hyperthyroidism*

Abstract: Modifications in characteristics and activities of beta-adrenergic receptors and certain parameters of the cyclic nucleotide systems were observed in the hypertrophied heart of the rat chronically treated with T4. These include: 1) an increased number of beta-adrenergic receptors without a change in their affinity, as determined by binding of (-)-[3H]dihydroalprenolol to the membrane; 2) increased sensitivity and magnitude of stimulation of adenylate cyclase in homogenates by isoproterenol, without a change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 0 publications
4
40
0
Order By: Relevance
“…Short term hyperthyroidism in the weanliig rat resulted in marked myocardial hypertrophy, a small but significant increase in Padrenergic receptor specific activity, no significant change in catecholamine dependent adenylate cyclase activation and more than doubling of the total /3-receptor number (per heart). The significance and mechanism of the lack of a n effect of hyperthyroidism on catecholamine-sensitive adenylate cyclase is unclear at present; however, the present finding is in general agreement with that reported in myocardium from adult hyperthyroid rats (17).…”
Section: E'supporting
confidence: 90%
See 3 more Smart Citations
“…Short term hyperthyroidism in the weanliig rat resulted in marked myocardial hypertrophy, a small but significant increase in Padrenergic receptor specific activity, no significant change in catecholamine dependent adenylate cyclase activation and more than doubling of the total /3-receptor number (per heart). The significance and mechanism of the lack of a n effect of hyperthyroidism on catecholamine-sensitive adenylate cyclase is unclear at present; however, the present finding is in general agreement with that reported in myocardium from adult hyperthyroid rats (17).…”
Section: E'supporting
confidence: 90%
“…Numerous studies have also supported the interrelationships among increased thyroid gland activity, increased P-adrenergic sensitivity and increased numbers of myocardial P-adrenergic receptors during hyperthyroidism (3,6,(16)(17)(18)21). Indeed, exposure of the myocardium to thyroid hormone in vitro and the administration of pharmacologic concentrations of thyroid hormones in vivo result in myocardial hypertrophy and increased number of P-adrenergic receptors in various myocardial preparations (3,6,(16)(17)(18)21). In addition, Tse et al (17) demonstrated increased catecholamine-sensitive adenylate cyclase activity, decreased cAMP phosphodiesterase and decreased c-GMP dependent protein kinase activity in ventricles from hyperthyroid rats (17).…”
Section: Speculationmentioning
confidence: 94%
See 2 more Smart Citations
“…Tse et al 19 also reported that the increase in adenyl cyclase activity in the hyperthyroid rat heart was not accompanied by a change in cyclic AMP content. The explanation offered for this phenomenon was that a lower intracellular concentration of ATP prevented a significant increase in cyclic AMP formation.…”
Section: Resultsmentioning
confidence: 94%